Configuration, Morphological, Syntactical and Syntagmatic Declination: Suggestion of a New Delimitation of Concepts - Rüdinger, Kurt (Revista de Filología Alemana, 2012)
The present article deals about the question, whether existing concepts of case may produce wrong ideas about the linguistic facts of modern western languages with Indoeuropean roots as well at an idiomatic level as in contrastive grammar. By defining the relation between configuration and morphological and syntagmatic declination a new model will be designed, able to resituate the corresponding phenomena in monolingual and contrastive approaches and bound to open new horizons in description and intermediation.